Analysis of language errors in narrative essays of fifth grade elementary school students - Nur Kamilah; Dilla Fadhillah; Sumiyani (Journal of Psychology and Instruction, 2022)
This study describes the errors in capital letters, words, and punctuation marks. This research uses a descriptive qualitative research method. The subjects of this study were fifth-grade students of SDN Karet 1. Data collection techniques using tests, interviews, and documentation. The results of this study, namely (1) errors in writing capital letters in the first letter of the title name amounted to 21 errors, the first letter of the name of the nation totaled 11 errors, the first letter of the name of the month amounted to 24 errors, and the first letter of the name of geography amounted to 29 errors. (2) the error of writing the preposition at- totaled 28 errors, and the error of writing the preposition to- amounted to 4 errors. (3) writing errors of period punctuation totaling 37 and comma punctuation totaling 15 errors.